Intimacies and Physiological Role of the Polymodal Cold-Sensitive Ion Channel trpm8 - Madrid-Montecinos, R; Pertusa-Pastor, M (Academic Press, 2014)
The detection of environmental temperature is critical for the survival of the most diverse organisms. Thermosensitive transient receptor potential (thermoTRP) channels have evolved as a class of ion channels activated by a wide range of temperatures. These molecular thermal sensors are spread through the different TRP channel subfamilies. Among the Melastatin subfamily of TRP channels, the eighth member, TRPM8, is a calcium-permeable cationic ion channel activated by cold, by substances that evoke cold sensation such as menthol, and by voltage. This channel is considered the main molecular entity responsible for the sensitivity to cold of primary sensory neurons of the somatosensory system. Here we present to the readers a summary of some the most relevant biophysical properties, physiological role, and molecular intimacies of this polymodal thermoTRP channel. © 2014 Elsevier Inc.